Regulative Structure of Locally Distributed Benefit Schemes and Inter-municipal Inequality: The Case of Estonia - Kriisk, Kersti (Studies of Transition States and Societies, 2019)
Studies of locally distributed social policy schemes, their central-local regulations and outcomes have mostly focused on single benefit schemes. However, the landscape of local social policy and access to social rights is more complex. Variety of local social policy schemes with various regulative structures can exist side-by-side within a welfare state, and often both central and local governmental levels have regulative powers for these. We assume that this complex web of central-local regulations of local social policy and changes thereof has consequences. In this study, we scrutinise regulative structures and spending patterns of all locally distributed benefit schemes in a given country (Estonia) and analyse their impact on inter-municipal inequality. We find that central steering of local schemes is not per se a guarantee for lower/stable inter-municipal inequality. The results also emphasise the complexity of central-local regulations within a country and point to unintended consequences of reforms. In the case of Estonia, we identify processes of silent centralisation in locally distributed benefit schemes.